Educational Robotics as a Tool for the Development of Algebraic Thinking at an Early Age (Docentes 2.0 Journal, 2020)
Developing algebraic thinking encourages the construction of more complex ideas, necessary for the formation of critical citizens, with well-founded arguments. Traditionally, the school has always trained in mathematical skills, however, the results have not favored most citizens. Educational plans in Mexico introduce algebraic topics, formally until secondary education, postponing early training for many years. The general objective was to explore educational robotics as a didactic resource aimed at developing algebraic thinking with students at an early age. A mixed methodology was implemented in a case study of five students aged 7 to 9 years, with a workshop belonging to the Autonomous University of Querétaro, Mexico. The proposal implemented a didactic sequence based on problem situations with robot assemblies, linking the subject of gears, together with direct proportionality. The most important finding was to identify educational robotics as a potential tool to favor the acquisition of algebraic concepts of unknown and variable in a functional relationship. Finally, educational robotics is positioned as a powerful didactic resource of the XXI century, in addition to combining various sciences, it makes it possible to work academic content outside the classroom, favoring cognitive development.
Keywords: Educational robotics; algebraic thinking; direct proportionality; didactic sequence